Hydro‐meteorological variability in the greater Ganges–Brahmaputra–Meghna basins - MD. Rashed Chowdhury; Neil Ward (International Journal of Climatology, 2004)
The flows of the Ganges, Brahmaputra and Meghna (GBM) are highly seasonal, and heavily influenced by monsoon rainfall. As a result, these rivers swell to their banks and often overflow during the monsoon months. This is most pronounced in the downstream regions, particularly in Bangladesh, which is the lowest riparian country. The objective of this paper is to study this hydro‐meteorological variability in the greater GBM regions, including the headwater regions in India and their role in streamflows in Bangladesh, and explore the large‐scale oceanic factors affecting this hydro‐meteorological variability. Global precipitation data, Bangladesh rainfall and streamflow records have been analysed and related to large‐scale climate patterns, including upstream rainfall, regional atmospheric circulation and patterns of sea‐surface temperature. The findings have quantified how the streamflows of these rivers in Bangladesh are highly correlated with the rainfall in the upper catchments with typically a lag of about 1 month. Therefore, streamflows in Bangladesh could be reasonably estimated for 1 to 3 months in advance (especially for the Ganges and Brahmaputra rivers) by employing simple correlation, if rainfall data from countries further up are available on a real‐time and continuous basis. In the absence of rainfall data, streamflow forecasts are still possible from unusually warm or cold sea‐surface temperatures in the tropics. The study concludes that hydro‐meteorological information flow between Bangladesh and other neighbouring countries is essential for developing a knowledge base for evaluating the potential implications of seasonal streamflow forecast in the GBM basins in Bangladesh. Copyright © 2004 Royal Meteorological Society

High‐resolution shallow seismic and ground penetrating radar investigations revealing the evolution of the Uemachi Fault system, Osaka, Japan - Mohamed Rashed; Koichi Nakagawa (Island Arc, 2004)
Ground penetrating radar (GPR) and high‐resolution shallow reflection seismic surveying were carried out to investigate the subsurface geology in and around the Uemachi Fault zone in the Yamato River area, Osaka, Japan. Shallow drilling in the area showed a major displacement event during the middle Pleistocene. The main Uemachi Fault plane could be clearly imaged on the seismic section, except for the most shallow 200 m. Several shallow normal fault planes with less displacement could be detected on both sides of the fault plane. GPR profiles confirmed the presence of several shallow normal faults within the area near the fault zone. These shallow faults could be followed in all of the GPR profiles crossing the fault zone. The integration of seismic section, GPR profiles and drilling data led to a conceptual model that explains the evolution of the Uemachi Fault system. The proposed model suggests the occurrence of several cycles of small vertical displacement along the deep part of the fault plane caused by the regional east–west compressional stress. The ductile nature of the shallow sedimentary cover and the absence of confining pressure in the shallow part allow for a considerable amount of plastic bending before failing in the shallow sedimentary layers. This bending generates stretching force within the shallow sedimentary cover, which in time, along with gravitational force, gives rise to the formation of the swarm of normal faults within the shallow layers near the fault zone. Some of the detected faults extend to a depth of less than 3 m below the ground surface, suggesting that the last tectonic activity along the fault plane may have occurred recently.

The evolution of locomotory behavior in profitable and unprofitable simulated prey - Thomas N. Sherratt; Arash Rashed; Christopher D. Beatty (Oecologia, 2004)